Development of 3D Snake and Ladder Media for Indonesian Language Learning: A Study of Pantun Education in Elementary School - Wijaya, Tri Bhakti Atma; Cahyaningtyas, Andarini Permata (Papanda Publisher, 2025)
This study aims to develop and test the effectiveness of 3D snake and ladder learning media to support fifth-grade elementary school students' Indonesian language learning outcomes. This development was motivated by the use of learning media that is still relatively simple, without games or more interesting concrete media. This lack of interesting media reduces student interest during learning, as seen from several students daydreaming, talking to their classmates, or playing alone while the teacher is explaining. This research uses the Research and Development (RnD) model ADDIE, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research was conducted in two stages: development and testing. The development stage includes problem analysis, literature review, initial 3D snake and ladder media development, and expert validation. The testing phase evaluated the effectiveness of the media on 20 fifth-grade students at Trangkilan State Elementary School. Initial data collection included documentation, interviews, questionnaires, and observations. The instruments used in this study included pretest-posttest to assess the effectiveness of the media and expert validation to assess the suitability of the developed media. Data analysis used normality tests, and paired t-tests. Expert validation results indicated that the 3D snake and ladder media was highly suitable for use, with an average score of 91%. Effectiveness tests showed a significant difference between pre-test and post-test scores (p < 0.05). The results of the pre-test and post-test of the students tested with the paired t-test showed that there was a difference in learning outcomes after the application of the 3D snake and ladder media in learning activities, so it can be concluded that the development of 3D snake and ladder media can support fifth-grade students in learning Indonesian language material on pantun at Trangkilan State Elementary School. The pre-test and post-test results showed an increase in the average scores obtained, with the pre-test average score being 54 and the post-test average score being 84. There was an improvement from using 3D Snakes and Ladders media in the learning activities. Furthermore, the level of effectiveness, as measured by Cohen’s d effect size, was 1.767 on a small scale and 2.112 on a large scale. This indicates that the learning intervention had a powerful impact on improving learning outcomes. Based on the research results, the 3D snake and ladder media is recommended for use in Indonesian language learning at elementary schools. This media is an attractive and innovative alternative to conventional media. The researcher recommends that this learning media be applied in learning, especially in fifth grade, to create meaningful learning.